Hubungan Interdialytic Weight Gain Terhadap Kualitas Hidup Pada Pasien Dengan Chronic Kidney Disease Di Unit Hemodialisis Rsu Royal Prima Medan Tahun 2024 - Damanik, Julia Yosida; Hasibuan, Kezia Chaterine; Valeri, Yolanda; Zega, Suci Christin; Addara, Cheriza; Kaban, Karmila (Jurnal Ners, 2025)
Interdialytic Weight Gain can also reduce patient health. The aim of the following study is to find out the relationship between Interdialytic Weight Gain and the survival of Chronic Kidney Disease patients in the Hemodialysis Unit of the Royal Prima University Hospital in Medan in 2024. The study used a quantitative research form with a cross-sectional research form where this study is a study where files are combined from a certain time from one group or sample. The samples taken were Chronic Kidney Disease patients who underwent hemodialysis at Royal Prima Hospital in Medan through the Accidental Sampling method. File review was carried out using univariate and bivariate analysis. The completion of the research that has been carried out on the Relationship of Interdialytic Weight Gain to Health of Life in Chronic Kidney Disease Patients in the Hemodialysis Unit of Royal Prima Hospital in Medan in 2024. Keywords: Chronics Kidneys Diseases , Hemodialysiss, Interdialytic Weight Gain, Quality of Life